Organizational wrongdoing: Bribery, fraud, cheating - Insights into the Herrenhausen Symposium, October 5-7, 2017 - Hustus, Ludmila; Schultze, Christin (Bribery, fraud, cheating, 2020)
The Herrenhausen Symposium, which took place at the Herrenhausen Palace in Hanover, Germany, on October 5–7, 2017, was a major platform for academic exchange about the phenomenon of organizational wrongdoing for scientists and practitioners from all over the world. As a complement to the project “The Fight against Corruption and Manipulation—Regulation and Self-Regulation in Medicine and the Economy”, organized by the research group for “Organizational Deviance Studies” from Heidelberg University and generously funded by the Volkswagen Foundation—the largest German private non-profit organization promoting research and education in sciences, social sciences and humanities, which is independent from the car manufacturer of the same name—, this symposium offered an excellent opportunity to shed light on bribery, fraud and cheating in various sectors as well as considering the different theoretical and practical perspectives while focusing on the key issues of these manifestations of organizational wrongdoing.
Gesehen am 03.11.2020